The development and convergence validity of the Malaysia Smell Test (MAST)/ Fatin Aishah Ramli and Akehsan Dahlan - Ramli, Fatin Aishah; Dahlan, Akehsan (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
An olfactory function is important role in our life. The function may decline as people get older. A smell test is a useful tool for predicting the onset of dementia. However, currently, many smell test developed in western country and not culturally appropriate in Malaysia. This study aims to develop and validate the Malaysia Smell Test (MAST) for older person in Malaysia. Besides, it also purposes to identify the relationship between the MAST with SLUMS-BM. A survey among elderly in the community (n=125) was obtained to identify the familiar odours remembered. The MAST kit was developed by using raw materials and 10 commonly odorants were selected. 38 participants from institutions were participated. All the data was analyzed by using SPSS version 21. It was revealed that there is moderate correlation between MAST and SLUMS-BM with (r=0.63) with ICC fair level of agreement (0.43) in which explain (80%) variance in the study. The MAST is easy to administer to the elderly because it’s short time, applicable, simple to administer and culturally appropriate in Malaysia as well as appears to recognize high risk of elderly and valuable tool for predicting the onset of dementia